THE EFFECT OF INQUIRY TRAINING LEARNING MODEL AND THE LOGICAL THINKING ABILITY ON SCIENCE PROCESS SKILL OF STUDENTS - Siti Aminah; Derlina . (Jurnal Pendidikan Fisika, 2015)
The purpose of this research was to analyze science process skill of students taught by training inquiry learning model better than taught by conventional learning, science process skill of students who have the  logical thinking ability above the average better than students who have the logical thinking ability below the average and analyze interaction between learning model and the logical thinking ability of students in influencing the science process skill of students. The research type was quasi experiment. The population was students Class X SMA Negeri 1 Tambangan Kabupaten Mandailing Natal. The cluster random class technique was used in choosing the research sample. The instruments were consists of the test of science process skill and the test of logical thinking ability of students. The used test to obtain the data was essay test. The data in this research was analyzed by using the two ways ANAVA analysis. The research result showed that science process skill of students taught by training inquiry learning model was better than students taught by conventional learning, science process skill of students who have the logical thinking ability above the average was better than students who have the logical thinking ability below the average, and there was interaction between learning model and logical thinking ability of students in influencing the science process skill of students.